INDEKS ATEROGENIK PLASMA DI PENYAKIT DIABETES MELITUS TIPE 2 (Atherogenic Index of Plasma in Type 2 Diabetes Mellitus) - Amarensi M Betaubun; Uleng Bahrun; Ruland Pakasi (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
Atherogenic Index of Plasma (AIP) as a new marker of atherogenicity and directly related to the risk of atherosclerosis, is a simpleand inexpensive method to assess the severity of atherogenic dyslipidemia. 97% of adult patients with type 2 DM (T2DM) will havedyslipidemia including increased levels of TG, low HDL-C levels whereas LDL cholesterol levels had no effect. To determine the atherogenicindex of plasma in controlled and uncontrolled T2DM. A Cross-sectional study was conducted on 72 controlled T2DM samples and 112uncontrolled T2DM samples from Clinic of Endocrine and Methabolic dr Wahidin Sudirohusodo Hospital Makassar, starting from April-May 2013. Fasting glucose level, triglycerides, HDL-C and HbA1c determined using ABX Pentra 400 (colorimetric method). Data thenanalyzed with Mann Withney U test. Most of the samples are male, with the age range from 51-60 years old. Mean AIP is not so differentbetween the two groups (0.51±0.28 and 0.55±0.28 respectively). Fasting glucose level, triglycerides, HDL-C in T2DM uncontrolled werehigher than controlled. The atherogenic index of plasma of controlled T2DM group were 0.93 times lower than uncontrolled T2DM, MannWithney U test showed that there were no significant correlation between both of group (p>0.05). Atherogenic index of plasma cannotbe used to distinguish between controlled and uncontrolled T2DM.